Effects of a Tax-Time Savings Experiment on Material and Health Care Hardship among Low-Income Filers. Issue 2 (4th March 2018) - Despard, Mathieu R.; Taylor, Samuel; Ren, Chunhui; Russell, Blair; Grinstein-Weiss, Michal; Raghavan, Ramesh
ABSTRACT: Material and health care hardship is common among households with low incomes and is associated with a host of adverse outcomes but can be mitigated with having savings. The authors assessed the effects of online tax-time savings interventions informed by behavioral economics on hardship among a sample of low- and moderate-income tax filers (N = 4, 738). The authors find that filers who received an intervention had a statistically significant, lower probability of both types of hardship 6 months after tax filing, compared to the control group. However, this result does not hold when incorporating household financial characteristics and prior hardship to models.